Deregulating School Aid in California How Districts Responded to Flexibility in Tier 3 Categorical Funds in 2010-2011 - Stecher, Brian M. (RAND Corporation, 2012)
Much of California's school funding is allocated through programs whose funding comes with requirements that districts use the money to support specific programs. In 2008-09, the strings were taken off 40 of these programs as part of a deal that also reduced their funding. This report presents the results of a survey of California's district chief financial officers (CFOs), describing how they made decisions in light of this new state policy.